Pengembangan Sistem Informasi Cuci Mobil Berbasiskan Website - Rohmah, Maghfirotur; Syafiih, M.; Hudawi AS, Ahmad (Rekayasa, 2021)
The car wash business is growing. A wide selection of car washes, spread across various regions. The increasing number of cars will provide more opportunities for entrepreneurs to open up in the car wash industry, while also providing entrepreneurs with potential for opportunities in the car market. With so many customers owned by Fuji Lestari, it is very risky for errors to update data every day, because the current transaction processes in the place of business still do not use computers, including in recording the number of consumers and this makes it difficult for Fuji Lestari to find data from files stored and archived by the company. From the problems that have been described, the researchers propose a website-based car wash information system. The waterfall method was chosen as the method in this research to achieve the expected goals. From the research that has been carried out by the author regarding the Web-Based Car Wash Information System at Fuji Lestari, several conclusions can be drawn, namely the Web-Based Car Wash Information System at Fuji Lestari has been produced, and after testing 5 users, from the results of calculating the total percentage obtained a percentage of 91%. Therefore, this information system is categorized as very good and suitable for use at Fuji Lestari car wash business.